Automatic power factor correction for single phase system - Muhd Isamuddin B. Ahmad Ritzzney (2015)
Power factor is the ratio of real power (W) and apparent power (VA). It is unit-less and measures how efficiently the current is being converted into real power. The power factor is a common problem for the most industrial companies. When the power factor is less than 0.85 for 132kV and below, it will result in increasing in reactive power (VAR). When reactive power is high, it will produce higher voltage drop. Due to this, power quality will decrease and will cause broken in electrical equipment or shorten the life of an equipment. Thus, consumer that have power factor below 0.85 will be charge power factor penalty in their electric bills. So, an improved power factor AC output is needed to overcome this problem. Usually, power factor correction was done manually by adjusting the capacitive bank, but this final year project focused on the automatic power factor correction by applying on the single phase system for maintaining the power quality through automatic capacitor switching. Finally, prototype of automatic power factor correction circuit is developed and the power factor detected is corrected through automatic capacitor switching circuit when the power factor is less than 0.9.